Kajian Kriminologi Terhadap Kejahatan Penyerobotan Tanah Di Wilayah Tulang Bawang - Muhammad Fhariedz Alfarizi Piin; Ahmad Irzal Fardiansyah; Emilia Susanti (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
Land grabbing is the act of taking rights or property arbitrarily or without paying attention to laws and regulations, such as occupying someone else's land or house to which they do not have rights. The act of illegally grabbing land is an act that is against the law, which can be classified as a criminal act. In connection with this case, this is the reason for the author to discuss the factors causing the crime of land grabbing in the Tulang Bawang area as well as efforts to overcome the crime of land grabbing. in the Tulang Bawang area. This research uses a normative juridical approach and is supported by an empirical juridical approach. Data collection was carried out using literature studies and field studies by conducting interviews with Tulang Bawang Sector Police officers, perpetrators and lecturers in the criminal law department at Lampung University, then the data was analyzed qualitatively. The results of the research and discussion show that the causes of land grabbing crimes in Tulang Bawang include environmental factors, weak self-control factors, family factors, and economic factors. Apart from that, efforts to overcome group fights are carried out through 2 (two) means, namely penal and non-penal. Penal measures are carried out only up to the point of reporting to the authorities. Meanwhile, non-penal efforts are carried out through mediation.